2004
DOI: 10.3923/pjn.2004.294.299
|View full text |Cite
|
Sign up to set email alerts
|

The Nutritional Evaluation of Locally Produced Dried Bakery Waste (DBW) in the Broiler Diets

Abstract: Due to the harsh environment of Saudi Arabia, yellow corn and soybean, the main energy and protein sources of the poultry diet are not successfully grown in this area. Therefore search for a locally produced alternative is of utmost important. Early studies suggested that bakery products could b e considered as energy substitute. Tons of dried bakery waste (DBW) are produced in the local bakeries of Saudi Arabia. This experiment was conducted to evaluate the use of dried bakery waste in the diets of broilers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Damron et al (1965) found that inclusion of up to 10% dried bakery product had no significant differences in body weights and feed conversion ratios as other 56-day-old broilers fed exclusively corn/soy. Al-Tulaihan et al (2004) also found that inclusion of up to 30% dried bakery waste had no significant differences in body weight, feed conversion ratio, and feed intake when compared to 42-day-old broilers fed exclusively corn/soy. Navidshad et al (2009) found that when broilers were provided meat meal at 65 and 80 g/kg feed in a corn/soy-based diet, they had comparable daily weight gain, daily feed intake, and feed conversion ratio to birds fed with a full corn/soy diet.…”
Section: Broiler Chicken and Food Wastementioning
confidence: 84%
See 2 more Smart Citations
“…Damron et al (1965) found that inclusion of up to 10% dried bakery product had no significant differences in body weights and feed conversion ratios as other 56-day-old broilers fed exclusively corn/soy. Al-Tulaihan et al (2004) also found that inclusion of up to 30% dried bakery waste had no significant differences in body weight, feed conversion ratio, and feed intake when compared to 42-day-old broilers fed exclusively corn/soy. Navidshad et al (2009) found that when broilers were provided meat meal at 65 and 80 g/kg feed in a corn/soy-based diet, they had comparable daily weight gain, daily feed intake, and feed conversion ratio to birds fed with a full corn/soy diet.…”
Section: Broiler Chicken and Food Wastementioning
confidence: 84%
“…A well formulated diet based on the requirements of the animal and the nutrient analyses of the feed ingredients may lead to increased feed conversion ratio in the animals. As demonstrated in multiple studies, broilers fed food waste at varying percentages had significantly similar performances when compared to a regular corn and soy diet (Table 3; Damron et al 1965;Al-Tulaihan et al 2004;Joshi et al 2000;Wadhwa et al 2013;Stefanello et al 2016). Table 3 includes waste products from multiple sectors of the food supply chain.…”
Section: Broiler Chicken and Food Wastementioning
confidence: 92%
See 1 more Smart Citation
“…Table (2) shows the effect of added dried bakery with and without yeast to the feed on the rate of weekly weight gain of broilers, it was noticed that there was a significant increase (P≤0.05) in the rate of weight gain in treatment T5, compared to parameters T1, T2, T3 and T4, which did not differ from each other significantly in the first week of life of the chicks.…”
Section: Weight Gainmentioning
confidence: 99%
“…Use dry bakery (dried) to feed poultry, produced in large quantities in Iraq, reaching tens of thousands of tons annually, it has a representative energy of about 3364 kilocalories/ kg, more energy than yellow corn, the crude protein content is 11.37%, lysine 0.35%, and methionine 0.23%, it does not contain anti-nutrients that inhibit poultry growth (Dabron et al, 1999). Leftover bakery is rich in vitamins, rich in energy and low in fiber, does not contain any antinutritional agent, better to use it to replace corn in broiler diets, it will benefit poultry producers and the poultry industry (Al-Tulaihan et al, 2004). Antibiotics are usually used in poultry production in order to obtain the best health and performance, some researchers have tried using antibiotics, it can be found naturally in bacteria and yeasts, but yeast has been proven to be more effective than others, as a source of probiotics to improve bird performance (Gaggia et al, 2010).…”
Section: Introductionmentioning
confidence: 99%